Career in Librarianships: Perceptions of First Year Undergraduate LIS Students of Federal University Dutsin-Ma, Katsina State, Nigeria - Hawwau A, Moruf; Salhu T.Salihu (IJoLIS, 2024)
PUrpose: This study sought to examine the perception of first year Library and ifnormation SCience(LIS) students in Feddral Universities Dutsin-Ma, Katsina State,Nigeria towards a career in Librarianship.